Neuraminidase treatment abrogates the binding abnormality of IgA1 from IgA nephropathy patients and the differential charge distribution of its alpha-heavy chains - Hashim, Onn Haji; Shuib, A.S.; Chua, C.T. (2001)
We have studied the interaction of the Gal-GalNAc-reactive champedak lectin-C with neuraminidase-treated and untreated IgA1 from IgA nephropathy patients. The binding ability of the lectin to untreated IgA1 from IgA nephropathy patients was significantly lower as compared to the untreated IgA1 from normal controls. This differential lectin-binding capacity was abrogated when the experiment was performed on neuraminidase-treated sera. Treatment of the serum IgA1 with neuraminidase also abrogated the differential charge distribution between the alpha -heavy chains of IgA nephropathy patients and normal controls. Copyright (C) 2001 S. Karger AG, Basel.